Immune cells employ intermittent integrin-mediated traction forces for 3D migration - Tina Czerwinski; Lars Bischof; David Böhringer; Sibel Kara; Pamela L. Strissel; Reiner Strick; Natalie Huhn; Alexander Winterl; Richard Gerum; Ernst Wittmann; Michael Schneider; Matthias W. Beckmann; et al. (Proceedings of the National Academy of Sciences, 2026)
To reach targets outside the bloodstream, immune cells can extravasate and migrate through connective tissue. During tissue infiltration, immune cells migrate in an amoeboid fashion, characterized by weak matrix adhesions and low traction forces, that allows them to achieve high migration speeds of up to 10 µm/min. How immune cells reconcile amoeboid migration with the need to overcome steric hindrance in dense matrices is currently not understood. Here we show that NK92 (natural killer) cells can switch from their default amoeboid migration mode to a contractile, mesenchymal-like migration mode when moving through fibrous human amniotic membrane (HAM) tissue. We subsequently study immune cell migration in reconstituted 3D collagen networks with known mechanical properties and pore sizes and apply time-lapse confocal reflection microscopy to obtain simultaneous measurements of migration speed, directional persistence, and cell contractility. We find that NK92 cells exert substantial acto-myosin driven, integrin-mediated contractile forces of up to 100 nN on the extracellular matrix during short contractile phases. This burst-like contractile behavior is also found in primary B, T, NK cells, neutrophils, and monocytes, and is tightly related to the fraction of cells that become stuck in narrow pores of the surrounding matrix. Our results demonstrate that steric hindrance guides the rapid regulation of integrin-mediated adhesion to the ECM in a large number of immune cell subtypes.